Moške zadeve? - Gutman, Maja (Monitor ISH, 2007)
The paper analyses the five-season series Queer As Folk, which had good ratings on the US Showtime, on Canadaćs Showcase, and later on a number of European channels. The analysis focuses on the cultural implications of QAF and raises the central question of the viewerćs position. It explores the shock effects of the series and the reasons for its surprising popularity, identifying the different possible ways of reading it by examining the criticisms which appeared while the series was running. Moreover, the paper argues that, its explicit content notwithstanding, QAF contains diverse elements which attract viewers regardless of their sexual preference. Some elements of this "catch-all" strategy are demonstrated as well.
Keywords: televizijske nadaljevanke; sociologija kulture; množična kultura; recepcija; potrošnja; kritika